Factors that influence the adoption of cell phone banking in South Africa - Sankar, Dione (My University, 2011)
Cell Phone Banking is a relatively new electronic banking channel which promised much in terms of servicing all banked customers, particularly those customer segments who don’t readily have access to the Internet. However, the adoption of Cell Phone Banking has been slow when compared to internet channel adoption and also to the growth of cell phone subscribers in the South African market. The purpose of this research was to identify the factors that influence the adoption of Cell Phone Banking in South Africa. The aim was to review the factors identified from previous research that could potentially influence the adoption Cell Phone Banking and to then test whether the identified proposed factors were applicable to the South African market. Data was collected via a survey questionnaire that was distributed physically to South African bank branches in Gauteng and to some identified corporate environments. A total of 174 surveys were collected, of which 153 responses were fully completed, and were used for the data analysis. The demographical and technology usage profiles were analysed and discussed using graphs. A confirmatory factor analysis was applied to the data collected to determine whether the factors proposed were relevant and applicable for the South African banking customer. It was found that the South Africa person most likely to adopt Cell Phone Banking was between the ages of 18 to 35, would have at least a Matric qualification (secondary education) and would earn at least a gross income of R100,000 per annum. It was concluded from the factor analysis that the five factors proposed namely perceived value, perceived risk, trialability, perceived credibility and perceived complexity, were indeed factors that would influence the adoption of Cell Phone Banking in South Africa. ii From the perceived value aspect, users perceived that convenience and time saving to be major items that influenced this factor. The perceived risk factor and perceived credibility factor highlighted that security and trust of the technology were major influencing factors towards the adoption of Cell Phone Banking respectively. The trialability factor was found to be important towards the adoption of Cell Phone Banking in South Africa. The reason provided for this was that customers wanted to have flexibility before actually being registered for the service. Lastly the factor of perceived complexity was also found to be important but compared to the other factors it was the least important factor. The reason provided for this was that the technology used for Cell Phone Banking was still relatively unknown and this was confirmed by the lack of understanding that the sample group showed when ranking the technologies in terms of ease of use.
MBA - WBS
Keywords: Cell phone banking; Mobile banking; Banks and banking